THE GIVING OF MASSAGE FRICTION AND ISCHEMIC COMPRESSIONTECHNIQUE ARE MORE EFFECTIVE THANMYOFASCIAL RELEASE TECHNIQUE FOR REDUCE TENSION HEADACE PAIN OF TEACHER STAFF IN SMK NEGERI 5 DENPASAR - Pramadita, I Gede Wisnu; Wibawa, Ari; Purnawati, Susy (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 2 (2017): Majalah Ilmiah Fisioterapi Indonesia, 2018)
Abstract   The combination of Massage Friction with Ischemic Compression Technique and Myofascial Release Technique is the intervention used and compared to reduce the pain of Tension   Headache on the teaching staff at SMKN 5 Denpasar.This research is experimental research with Randomized Purposive Sampling design. The sample consists of 18 people divided into 2 groups. Treatment Group 1 was given Intervention Massage Friction and Ischemic Compression Technique and Treatment Group 2 was given Myofascial Release Technique Intervention. The mean difference of Tension Headache headache decrease in treatment group 1 was 1.00 and in treatment group 2 was 0.46 with (p <0,05). It was concluded that the Massage Friction and Ischemic Compression Technique Intervention was more effective than Myofascial Release Technique in reducing Tension Headache headache on the teaching staff at SMKN 5 Denpasar.   Keywords : Tension Headache, Massage Friction, Ischemic Compression Technique, Myofascial Release Technique